The critical nexus : tone-system, mode, and notation in early medieval music - Atkinson, Charles M. (Charles Mercer), 1941- (AMS studies in music., 2009)
Prologue. 1. The Heritage of Antiquity. Part I. The Eighth and Ninth Centuries. 2. The Reception of Ancient Texts in the Carolingian Era. 3. The Heritage of the Church. Part II. The Synthesis of Ancient Greek Theory and Medieval Practice. 4. Hucbald of St. Amand and Regino of Prum. 5. Alia musica. 6. Pseudo-Bernelinus, Pseudo-Odo, and Guido d'Arezzo. Epilogue: Problems and Solutions. Bibliography. Index.